C♯ design patterns : a tutorial - Cooper, James William, 1943- (Addison-Wesley, 2003)
Design patterns are elegant, adaptable, and reusable solutions to everyday software development problems. Programmers use design patterns to organize objects in programs, making them easier to write and modify. C# Design Patterns: A Tutorial is a practical guide to writing C# programs using the most common patterns. This tutorial begins with clear and concise introductions to C#, object-oriented programming and inheritance, and UML diagrams. Each chapter that follows describes one of twenty-three design patterns, recommends when to use it, and explains the impact that it will have on the larger design. The use of every pattern is demonstrated with simple example programs. These programs are illustrated with screen shots and UML diagrams displaying how the classes interact. Each of these programs is available on the companion CD-ROM and can be run, examined, edited, and applied. Design patterns will have an immediate impact on your work as you learn the following: Applying design patterns effectively in your day-to-day programming Using patterns to create sophisticated, robust C# programs The interaction of classes as demonstrated by UML diagrams Advancing your programming skills using design patterns Design patterns will not only enhance your productivity, but once you see how quickly and easily object-oriented code can be recycled, they will become an everyday part of your C# programming. 0201844532B05232002.